Competitive forests – tenure revisited - T. Rotherham; K. Armson (The Forestry Chronicle, 2018)
This paper reviews changes in the management and use of Canadian forests from the early days as a source of timber for ship building, logs for lumber, then to fibre for pulp & paper mills, and more recently, back to logs for lumber production with sawmill residues becoming the main source of raw materials for production of pulp & paper and wood pellets. The adoption of sustainable forest management by society and governments has influenced the development and regulation of forest management, including certification programs with SFM standards, independent third-party audits and certification. There are two forms of tenure on provincial lands: Volume Agreements and Area Agreements. At the present time, neither offer real incentives to promote tree growth or enhance tree quality through long-term silvicultural treatments. Area Agreements perhaps hold the most promise, ones where forest tenure and management are rooted in the communities surrounded by and dependent on the forests they manage. The provision of secure, long-term tenure may provide the incentives to support long-term planning, including investment in silvicultural treatments to improve growth and tree quality needed to support a competitive industry.